An evolutionarily-conserved promoter allele governs HMG-CoA reductase expression in spontaneously hypertensive rat. (September 2021) - Khan, Abrar A.; Sundar, Poovitha; Natarajan, Bhargavi; Gupta, Vinayak; Arige, Vikas; Reddy, S. Santosh; Barthwal, Manoj K.; Mahapatra, Nitish R.
Abstract: 3-Hydroxy-3-methyl glutaryl-coenzyme A reductase ( Hmgcr ) encodes the rate-limiting enzyme in the cholesterol biosynthesis pathway. The regulation of Hmgcr in rat models of genetic hypertension (viz. Spontaneously Hypertensive Rat [SHR] and its normotensive control Wistar/Kyoto [WKY] strain) is unclear. Interestingly, Hmgcr transcript and protein levels are diminished in liver tissues of SHR as compared to WKY. This observation is consistent with the diminished plasma cholesterol level in SHR animals. However, the molecular basis of these apparently counter-intuitive findings remains completely unknown. Sequencing of the Hmgcr promoter in SHR and WKY strains reveals three variations: A-405G, C-62T and a 11 bp insertion (‐398_-388insTGCGGTCCTCC) in SHR. Among these variations, A-405G occurs at an evolutionarily-conserved site among many mammals. Moreover, SHR- Hmgcr promoter displays lower activity than WKY- Hmgcr promoter in various cell lines. Transient transfections of Hmgcr -promoter mutants and in silico analysis suggest altered binding of Runx3 and Srebf1 across A-405G site. On the other hand, C-62T and -398_-388insTGCGGTCCTCC variations do not appear to contribute to the reduced Hmgcr promoter activity in SHR as compared to WKY. Indeed, chromatin immunoprecipitation assays confirm differential binding of Runx3 and Srebf1 to Hmgcr promoter leading to reduced expression of Hmgcr in SHR as compared to WKY under basal as well as cholesterol-modulated conditions. Taken together, this study provides, for the first time, molecular basis for diminished Hmgcr expression in SHR animals, which may account for the reduced circulating cholesterol level in this widely-studied model for cardiovascular diseases. Graphical abstract: Unlabelled Image Highlights: Hepatic Hmgcr transcript and protein levels are diminished in SHR as compared to WKY. The diminished Hmgcr expression is mediated by an evolutionarily-conserved allele in the SHR-Hmgcr promoter. Runx3 and Srebf1 differentially interact with the Hmgcr promoter in SHR versus WKY. Intracellular cholesterol level also regulates Hmgcr expression via Runx3 and Srebf1. Multiple genetic rodent models of hypertension including SHR exhibit diminished serum cholesterol level.